Needs of Student with Educational Management of Rajamangala University of Technology Lanna Chiang Rai - Thipprasert, Natcha; Chompoomeang, Seangdaun; Panyo, Jariya (Journal of Advanced Development in Engineering and Science, 2023)
This research was to study needs of student with educational management of Rajamangala University of Technology Lanna Chiangrai in order to serve as a guide for development and improvement teaching activities and learning facilities in various fields to be more effective and meet the needs of the students. 1,392 subjects drawn from HCU undergraduate students of the Rajamangala University of Technology Lanna Chiangrai are the sample of this research. The tool used for collecting data is a questionnaire that its reliability is equivalent to 0.92. The statistical technique used for analysis of the detail is one way ANOVA. The results showed that in the part of personal characteristics of the sample, the major percentages of 58.19 are females being over 20 year old of 61.85 percent and 78.52 percent of sample are in the undergraduate. Needs of student with educational management of Rajamangala University of Technology Lanna Chiangrai are in the high level with mean of 3.54. When the individual aspects of needs was considered, it was found that the aspects of teacher, content, teaching methods, measurement and evaluation, the teaching and learning and audiovisual are in the high level of needs with a mean of 3.74 followed by locations which are in the moderate level of needs.